An Aplication of Activity based Costing in Determining Tuition Fees in Gembala Baik Junior High School Pontianak - B42111010, Merie Anne B42111010 meri (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Abstract